Autologous liver transplantation – experience of the Republican Clinical Hospital of Kazan - A. A. Kirshin; L. I. Ziganshin; B. A. Sakhabetdinov; V. I. Shpaner; A. R. Ibragimova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Currently, autologous organ transplantation continues to be widely implemented in various countries. Its relevance is due to the large number of patients with diffuse liver damage. Liver autotransplantation is an effective and only radical operation for end-stage diffuse liver lesions, such as alveococcosis, cholangiocellular carcinoma and metastatic liver cancer.Purpose of the study. To evaluate the results of the clinical implementation of liver autotransplantation technologies in the State Autonomous Healthcare Institution of the Republican Clinical Hospital.Materials and methods. Since 2023, 4 operations for liver autotransplantation have been performed in the State Autonomous Healthcare Institution of the Russian Clinical Hospital. One patient was selected to describe the clinical case.Research results. The operation for autologous liver transplantation in a patient with alveococcosis of the left lobe of the liver was performed successfully on December 4, 2023. On day 45, the patient was discharged for outpatient observation in satisfactory condition.Conclusion. The complexity of liver transplantation and resection due to the lack of donor organs and the high risk of rejection forces the introduction of new, more effective methods, one of which is liver autotransplantation, which does not require immunosuppressive therapy, which reduces the risk of developing purulent-inflammatory complications in the postoperative period.